If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(t + 2) + -3(t + -4) = -3(5y + -7) + 8 Reorder the terms: 8(2 + t) + -3(t + -4) = -3(5y + -7) + 8 (2 * 8 + t * 8) + -3(t + -4) = -3(5y + -7) + 8 (16 + 8t) + -3(t + -4) = -3(5y + -7) + 8 Reorder the terms: 16 + 8t + -3(-4 + t) = -3(5y + -7) + 8 16 + 8t + (-4 * -3 + t * -3) = -3(5y + -7) + 8 16 + 8t + (12 + -3t) = -3(5y + -7) + 8 Reorder the terms: 16 + 12 + 8t + -3t = -3(5y + -7) + 8 Combine like terms: 16 + 12 = 28 28 + 8t + -3t = -3(5y + -7) + 8 Combine like terms: 8t + -3t = 5t 28 + 5t = -3(5y + -7) + 8 Reorder the terms: 28 + 5t = -3(-7 + 5y) + 8 28 + 5t = (-7 * -3 + 5y * -3) + 8 28 + 5t = (21 + -15y) + 8 Reorder the terms: 28 + 5t = 21 + 8 + -15y Combine like terms: 21 + 8 = 29 28 + 5t = 29 + -15y Solving 28 + 5t = 29 + -15y Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-28' to each side of the equation. 28 + -28 + 5t = 29 + -28 + -15y Combine like terms: 28 + -28 = 0 0 + 5t = 29 + -28 + -15y 5t = 29 + -28 + -15y Combine like terms: 29 + -28 = 1 5t = 1 + -15y Divide each side by '5'. t = 0.2 + -3y Simplifying t = 0.2 + -3y
| 9+11x-7=9x+18-2x | | -2(p-5)+5p=-5 | | 4X+32Y=-16 | | 4+12a=22+6a | | 7a-3x= | | 8(t+2)-3(t-4)=-3(5y-7)-8 | | -1/9(x-27)+1/3(x+3)=x+11 | | y=-5/3x+7 | | 6/3 | | (y-9)-(y+1)= | | 15-0.75a=13-0.5a | | 6/8 | | 1/2-5/8x=7/8x+7/2 | | 330000=3x | | y=4-7x | | 2z-4(9-32)=62 | | 9(5)= | | 10=4-1x | | 6x^2-5x=2x+3 | | 125x^6+216g^3= | | -8=-2(c+1) | | 4r^2*4= | | 8x-5-3x=-15 | | 6x(2)-5x=2x | | X/7+4/7-x/5-3/5=4 | | 2x+1/2y=6 | | Y-160=-81/2(X-0) | | X+4/7-x-3/5=4 | | 1/6x=491/6 | | 30a=80+22a | | 4r^2*r= | | 6(x)=8x-3 |